2016
DOI: 10.1177/1066480716670141
|View full text |Cite
|
Sign up to set email alerts
|

The Possible Trajectory of Relationship Satisfaction Across the Longevity of a Romantic Partnership

Abstract: This cross-sectional research investigation examined how relationship satisfaction varies as individuals in romantic partnerships become parents, as subsequent children join the family, and as children age. Results indicated individuals in romantic partnerships without children report greater, overall, levels of relationship satisfaction, more affectional expression than those with two children, and greater couple cohesion compared to those with three children. Of all the individuals in romantic partnerships w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 33 publications
1
14
1
Order By: Relevance
“…Previous research also indicates no association between the number of children or parenthood and infidelity, although the available studies are either limited to non-married individuals, used the actual number of children as predictors, while none of the studies focused on fatherhood, relationship satisfaction, and infidelity [31][32][33][34]. However, relationship satisfaction of the couple commonly declines as soon as the child is born [26,27,63]. Furthermore, fathers show an increase in depressive symptoms during the first phase after birth and a residual amount of symptomatology over the first seven years of their child's life [64][65][66].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research also indicates no association between the number of children or parenthood and infidelity, although the available studies are either limited to non-married individuals, used the actual number of children as predictors, while none of the studies focused on fatherhood, relationship satisfaction, and infidelity [31][32][33][34]. However, relationship satisfaction of the couple commonly declines as soon as the child is born [26,27,63]. Furthermore, fathers show an increase in depressive symptoms during the first phase after birth and a residual amount of symptomatology over the first seven years of their child's life [64][65][66].…”
Section: Discussionmentioning
confidence: 99%
“…For men, the frequency of sex is significantly more relevant than for women and that infrequent sex is associated with sexual and relationship dissatisfaction in men, but not women [67]. Although, it is known that paternity has several negative consequences for the relationship and the sexual life of fathers and mothers, this is more likely in couples with small children, while couples with older children such as eight years or older do not experience the same challenges anymore and regain some of the lost relationship and sexual satisfaction [63]. On the other hand, it has also been suggested that in couples without children, relationship satisfaction is very low, the relationship is terminated more quickly, while parents are more likely to stay together despite difficulties for the sake of the children [68].…”
Section: Discussionmentioning
confidence: 99%
“…For parents, this decline may be steeper. Indeed, couples without children have a higher quality of romantic relationship compared to parents (Meyer, Robinson, Cohn, Gildenblatt, & Barkley, 2016), and the transition to parenthood is linked to a decrease in the quality of the romantic relationship (Keizer & Schenk, 2012; Kluwer, 2010; Twenge, Campbell, & Foster, 2003). This population therefore appears to be at greater risk of experiencing the negative consequences of a low-quality romantic relationship.…”
Section: Development Of the Romantic And Coparental Relationshipsmentioning
confidence: 99%
“…For example, Claxton and Perry‐Jenkins () found initial declines in shared leisure time between spouses during the transition to parenthood in dual‐earning couples; although shared leisure time began to increase through the year after birth, upon a 1‐year follow up, shared leisure time was still significantly lower than prenatal levels. Relatedly, multiple studies document declines in relationship satisfaction and general functioning across the transition to parenthood (Meyer, Robinson, Cohn, Gildenblatt, & Barkley, ; Nomaguchi & Milkie, ), associated with declines in quality time spent together after the birth of a child (Claxton & Perry‐Jenkins, ; White, Booth, & Edwards, ). The findings in our study may point to higher levels of differentiation of self as a noteworthy protective factor from relationship maladjustment during relationship transitions when couple leisure quality may be diminished.…”
Section: Discussionmentioning
confidence: 99%